An Intensive Care Unit Outbreak of Acute Respiratory Distress Syndrome due to Human Metapneumo Virus Infection - Ankur Sinha MBBS; Vignesh Ponnusamy MBBS; Sushilkumar S. Gupta MBBS; Hitesh Raheja MBBS; Ravikaran Patti MBBS; Parita Soni MBBS; Namrita Malhan BDS; Yu Shia Lin MD; Yizhak Kupfer MD (SAGE Publishing, 2019)
Human metapneumo virus is an emerging cause of upper and lower respiratory tract illness with increasing reports of a varied spectrum of disease over all age groups. We report an outbreak of 6 cases of human metapneumo virus infection in the intensive care unit of a metropolitan tertiary care center over 6 weeks, leading to severe acute respiratory distress syndrome. We report the subsequent favorable outcomes due to the institution of extracorporeal membrane oxygenation.